Analysis program in reducing the number of under – fives under red line at sarudik public health center working area - Tinawati Nainggolan (Science Midwifery, 2023)
Based on data obtained from the Public Health Center, the number of toddlers in the Sarudik Health Center is 1,201 people and there are 9 toddlers with a Weight Below the Red Line (BGM). The purpose of the study is to determine the facilities and infrastructure, human resources and the achievement of the implementation of the Puskesmas Program in Reducing the incidence of Toddlers with Weights Below the Red Line. The research method used is qualitatively with appropriate methods and adequacy. This research was conducted by means of in-depth interview methods, data collection tools in the form of recording, cameras, stationery and interview guidelines. The results of this study are the existing human resources at the Sarudik Health Center are in accordance with the standards, and the facilities and infrastructure at the Sarudik Health Center in the malnutrition prevention program are also appropriate and the implementation of care for undernourished children under five has gone well, namely by carrying out home visits and people Parents come to the posyandu, conduct counseling and counseling on toddler nutrition, and the provision of PMT has also been carried out according to what initially toddlers experience malnutrition, there are already toddlers who are improving with increased body weight than before because they are routinely monitored and monitored, especially the midwife in charge.